Exploring the smallholder irrigation equipment supply landscape in Zambia: a scoping review - Choruma, Dennis Junior; Dirwai, Tinashe Lindel; Matchaya, Greenwell C.; Kasoma-Pele, Winnie; Mutenje, Munyaradzi (Springer, 2025)
Limited irrigation adoption hinders agricultural production for Zambia's smallholder farmers, despite its potential to mitigate the impact of erratic rainfall patterns. This scoping review investigates the irrigation equipment supply landscape in Zambia, focusing on its capacity to serve smallholders. Using the PRISMA framework, the review explores the range of available irrigation technologies, the technical knowledge of suppliers, and the challenges and opportunities surrounding equipment supply. The review identifies affordability of irrigation equipment, uneven distribution of technical support and spare parts, and limited access to credit and market opportunities as key challenges hindering smallholder farmers’ irrigation adoption. However, opportunities exist through geographic targeting, collaboration with development initiatives and supermarkets, and improved access to financing. By addressing these challenges and capitalizing on opportunities, stakeholders can empower smallholder farmers to adopt irrigation technologies and achieve increased production.